Pengaruh Modal Intelektual terhadap Kinerja Keuangan dan Nilai Pasar - Dwi Artati (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2017)
This research aims to observe, analyze effect of intellectual capital (VAIC) to financial performance delegated by ROE and market value delegated by M/B (Market to Book Value Ratio), and test the difference intellectual capital (VACA, VAHU, STAVA) at manufacture, trading and financial industry. In addition to, this research observes difference indication of intellectual capital effect to financial performance and market value among manufacture, trading and financial industry. The sample which used was manufacture companies, trading and financial industries at BEI in 2011-2013. This research used company size as control variable delegated by asset. The method of data collecting was done by conducting documentation secondary data using the financial statement of manufacture, trading, and financial companies at BEI and other seconder data. The method of analyses which used weremultiple linier regression analyses, F test, t test, One Way Anova and chow test. The instrument statistik which used was SPSS 22. Based on the findings, it can be concluded that VACA and STAVA affect financial performance (ROE), whereas VAHU doesn’t. Then, VAHU affects market value, whereas VAHU and STAVA don’t. Furthermore, the test of difference of intellectual capital (VACA, VAHU, STAVA) at three companies, such as manufacture, trading and financial industries showed that there was a difference among them. Meanwhile, the verification showed that there is difference the effect of intellectual capital (VACA, VAHU, STAVA) to financial performance and market value. Key words : intellectual capital, VACA, VAHU, STAVA, ROE, M/B, company standard